Bifidobacterium longum, a Predominant Bifidobacterium in Early-life Infant Potentially Used as Probiotic - Kusharyati, Dyah Fitri; Rovik, Anwar; Ryandini, Dini; Pramono, Hendro (Biosaintifika: Journal of Biology & Biology Education, 2020)
In early life, Bifidobacteria are reported as dominant bacteria in the human digestive tract. Bifidobacterium is potential as a probiotic. The probiotic property of Bifidobacterium is strain-specific. This study aimed to identify the Bifidobacterium (isolated from less than one-month-old healthy infant stool that potentially used as probiotic) based on the 16S rRNA gene and determining their similarities among Bifidobacteria. The probiotic-potentially Bifidobacterium was re-characterized by performing a Gram’s staining and catalase test. The DNA extraction process was followed by the 16S rRNA amplification using 27F-1492R primers. Sequence similarity was checked by using the BLAST program in the GenBank. The phylogenetic tree was constructed by using a neighbor-joining (NJ) method within the MEGA version 7.0 package. The 16S rRNA gene was presented at 1,500 bp length. Bifidobacterium strains have a 91.14-94.26 % sequence similarity to B. longum subsp. longum strain CCUG30698 which is considered as insufficient for species and genus identifications. However, those isolates could be assigned in a phylogenetic position. This present study suggested the B. longum as the dominant strain of Bifidobacterium in the gut of early-life infants which has potential as a probiotic and is considered as an ideal probiotic for human consumption. This study is useful as basic information for other related research, as well as its application in industrial or community service fields.